Biophysical characterisation of calumenin as a charged F508del-CFTR folding modulator. - Rashmi Tripathi; Nathalie Benz; Bridget Culleton; Pascal Trouvé; Claude Férec (PLoS ONE, 2014)
The cystic fibrosis transmembrane regulator (CFTR) is a cyclic-AMP dependent chloride channel expressed at the apical surface of epithelial cells lining various organs such as the respiratory tract. Defective processing and functioning of this protein caused by mutations in the CFTR gene results in loss of ionic balance, defective mucus clearance, increased proliferation of biofilms and inflammation of human airways observed in cystic fibrosis (CF) patients. The process by which CFTR folds and matures under the influence of various chaperones in the secretory pathway remains incompletely understood. Recently, calumenin, a secretory protein, belonging to the CREC family of low affinity calcium binding proteins has been identified as a putative CFTR chaperone whose biophysical properties and functions remain uncharacterized. We compared hydropathy, instability, charge, unfoldability, disorder and aggregation propensity of calumenin and other CREC family members with CFTR associated chaperones and calcium binding proteins, wild-type and mutant CFTR proteins and intrinsically disordered proteins (IDPs). We observed that calumenin, along with other CREC proteins, was significantly more charged and less folded compared to CFTR associated chaperones. Moreover like IDPs, calumenin and other CREC proteins were found to be less hydrophobic and aggregation prone. Phylogenetic analysis revealed a close link between calumenin and other CREC proteins indicating how evolution might have shaped their similar biophysical properties. Experimentally, calumenin was observed to significantly reduce F508del-CFTR aggregation in a manner similar to AavLEA1, a well-characterized IDP. Fluorescence microscopy based imaging analysis also revealed altered trafficking of calumenin in bronchial cells expressing F508del-CFTR, indicating its direct role in the pathophysiology of CF. In conclusion, calumenin is characterized as a charged protein exhibiting close similarity with IDPs and is hypothesized to regulate F508del-CFTR folding by electrostatic effects. This work provides useful insights for designing optimized synthetic structural correctors of CFTR mutant proteins in the future.